2022
DOI: 10.1111/and.14409
|View full text |Cite
|
Sign up to set email alerts
|

The association of impaired semen quality and pregnancy rates in assisted reproduction technology cycles: Systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Accordingly, ICSI rather than IVF has been commonly suggested in cases of reduced normal morphology or severe teratozoospermia (< 5%) 46 . Notwithstanding, several studies have reported that the clinical pregnancy rates in couples in which the male partner had severe teratozoospermia did not change according to the method of insemination 35,37,47–49 . Keegan et al 38 .…”
Section: Search Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, ICSI rather than IVF has been commonly suggested in cases of reduced normal morphology or severe teratozoospermia (< 5%) 46 . Notwithstanding, several studies have reported that the clinical pregnancy rates in couples in which the male partner had severe teratozoospermia did not change according to the method of insemination 35,37,47–49 . Keegan et al 38 .…”
Section: Search Methodsmentioning
confidence: 99%
“…46 Notwithstanding, several studies have reported that the clinical pregnancy rates in couples in which the male partner had severe teratozoospermia did not change according to the method of insemination. 35,37,[47][48][49] Keegan et al 38 in a retrospective study of 495 couples undergoing ART treatments with IVF and ICSI, in whom the male partners were diagnosed with teratozoospermia, found no statistical difference in fertilization, FF, pregnancy, and LBR. Finally, Hotaling et al confirmed this finding in a large study including about 3000 IVF/ICSI treatments, concluding that the use of ICSI rather than IVF yields no difference in pregnancy outcomes in patients with severe teratozoospermia.…”
Section: Icsi In Cases Of Borderline Semen Assessment (Oligo-astheno-...mentioning
confidence: 99%
“…IVF and later IVF-ICSI were developed in order to achieve pregnancy even in the most severe forms of male infertility. A recent meta-analysis has shown that semen quality, as assessed by a standard semen analysis, does not impact IVF and ICSI pregnancy rates [17]; in the past several years, we see a rise in the use of IVF/ICSI to overcome male factor [18].…”
Section: Varicocele Repair and In-vitro Fertilizationmentioning
confidence: 99%
“…The decline in fertility in both males and females and the trend of delaying pregnancy to a later age have promoted the development of ARTs [ 17 ]. However, the moderate success rate of pregnancy and the unclear mechanisms behind it are hindering the wide use of ARTs [ 122 ]. In addition, some studies observe a higher risk of adverse outcomes in ART-conceived babies (and animals) than in naturally conceived ones [ 123–126 ], pushing us to update our understanding in this area.…”
Section: Reproductive Tract Microbiome and Artsmentioning
confidence: 99%